Implementing the active lifestyle program for students: the “Fortaleça Sua Saúde” - Iraneide Etelvina Lopes; Jair Gomes Linard; Magna Leilane da Silva; Valter Cordeiro Barbosa Filho (Revista da Educação Física)
This study aimed to evaluate the implementation of an intervention program to promote active and healthy lifestyle in students. This was a evaluation study performed during the intervention, which included the school community (students, teachers, coordinators and parents), through interview or external observation. The evaluation matrix was constructed and validated with 32 measures in eight indicators: teacher training, modification in Physical Education classes, modification in regular classes, distribution of pamphlets, distribution of material, gymnastics in the school, visibility of the program and knowledge and distribution of material. Descriptive (quantitative) or content (qualitative) analysis was used. Health issues in the classroom were addressed by 94% of teachers during the intervention. Half of the students reported that they participated in at least one gym class and used the games during the intervention, but difficulties in storage of sports equipments and organization of places were reported. Knowledge about the program was frequent among teachers, managers and students, but not between parents. In conclusion, most of the program actions had an implementation as planned, however, difficulties were reported and should be considered in future proposals of a school environment that aims to promote physical activity and health.